Объяснение:
1) 3Ca(NO3)2+2Na3PO4=Ca3(PO4)2+6NaNO3
3Ca(2+)+6NO3(-)+6Na(+)+2PO4(3-)=Ca3(PO4)2+6Na(+)+6NO3(-)
3Ca(2+)+2PO4(3-)=Ca3(PO4)2
2) Mg(OH)2+2HCl=MgCl2+2H2O
Mg(OH)2+2H(+)+2Cl(-)=Mg(2+)+2Cl(-)+2H2O
Mg(OH)2+2H(+)=Mg(2+)+2H2O
3) K2SO3+2HNO3=2KNO3+SO2+H2O
2K(+)+SO3(2-)+2H(+)+2NO3(-)=2K(+)+2NO3(-)+SO2+H2O
SO3(2-)+2H(+)=SO2+H2O
4) Fe2O3+6HCl=2FeCl3+3H2O
Fe2O3+6H(+)+6Cl(-)=2Fe(3+)+6Cl(-)+3H2O
Fe2O3+6H(+)=2Fe(3+)+3H2O
5) ZnSO4+2KOH=Zn(OH)2+K2SO4
Zn(2+)+SO4(2-)+2K(+)+2OH(-)=Zn(OH)2+2K(+)+SO4(2-)
Zn(2+)+2OH(-)=Zn(OH)2
6) SO3+2NaOH=Na2SO4+H2O
SO3+2Na(+)+2OH(-)=2Na(+)+SO4(2-)+H2O
SO3+2OH(-)=SO4(2-)+H2O
Mg+Cl2=MgCl2
Mg(0)+Cl2(0)=Mg(2+)+2Cl(-)
MgCl2+2NaOH=Mg(OH)2+2NaCl
Mg(2+)+2Cl(-)+2Na(+)+2OH(-)=Mg(OH)2+2Na(+)+2Cl(-)
Mg(2+)+2OH(-)=Mg(OH)2
Mg(OH)2+2HNO3=Mg(NO3)2+2H2O
Mg(OH)2+2H(+)+2NO3(-)=Mg(2+)+2NO3(-)+2H2O
Mg(OH)2+2H(+)=Mg(2+)+2H2O
Mg(NO3)2+Na2CO3=MgCO3+2NaNO3
Mg(2+)+2NO3(-)+2Na(+)+CO3(2-)=MgCO3+2Na(+)+2NO3(-)
Mg(2+)+CO3(2-)=MgCO3
MgCO3+H2SO4=MgSO4+CO2+H2O
MgCO3+2H(+)+SO4(2-)=Mg(2+)+SO4(2-)+CO2+H2O
MgCO3+2H(+)=Mg(2+)+CO2+H2O
1)Ch4+cl2=ch3cl+hcl
2)ch3cl+na-ch3-ch3+nacl
3)ch3-ch3(t)=ch2=ch2+h2
4)ch2=ch2+hcl=ch2cl-ch3
5)ch2-ch3+cl2=ch2cl-ch2cl+hcl Этан ch3-ch3(t)=ch2=ch2+h2(этилен)
|
cl ch2=ch2+3o2=2co2+2h2o(углекислый газ)
ch2=ch2+hoh=ch2-ch2
|
oh
1B 2A 3Г 4Б
B11
1) MgO + 2HNO3
2) Ca + 2HCl
3) K2O + H3PO4
4) Na2O + H2S
B12
1) Li2SO4 + H2O
2) K3PO4 + H2O
3) CaCO3 + 2H2O
4) BaSO3 + H2O